Disabilities concessions in Indonesia: fundamental problems and solutions - Permatasari, Ristania Intan; Hermawan, Sapto; Jaelani, Abdul Kadir (Faculty of Law, University of Muhammadiyah Malang, 2022)
There are many people with disabilities in Indonesia. However, the government has not fulfilled the rights of persons with disabilities according to the provisions in the laws and regulations on persons with disabilities. This study aims to analyze concessions for persons with disabilities in Indonesia: fundamental problems and offered solutions. This research is a normative study using the Literature Review study approach, namely by examining and analyzing data. The results of the research show that the government has not guaranteed the rights of persons with disabilities in Indonesia, so it is essential to issue government regulations that regulate the type and amount of concessions as a form of creating legal certainty for persons with disabilities. This concession is essential to implement in Indonesia because it can reduce the barriers for persons with disabilities to access essential services to increase their income and economic participation.